Peripheral visual perception during exercise: Why we cannot see - Soichi, A. (Exercise and Sport Sciences Reviews, 2013)
Peripheral visual perception may be relevant to performance in sports. Peripheral visual perception seems to be impaired during strenuous exercise. The hypothesis proposed is that a decrease in cerebral oxygenation is associated with impairment in peripheral visual perception during strenuous exercise. Recent behavioral and physiological data are presented to support the hypothesis.